FTIR and UV-Visible Spectral Study on Normal and Diseased Blood Samples - Gunasekaran, S.; Sankari, G. (Asian Journal of Chemistry, 2016)
The application of spectroscopy for the study of biomedical compounds has increased tremendously in recent years. Blood is the chief circulatory medium in our body and participates in every functional activity by virtue of its circulation through every organ. The study of blood is one of the fascinating branches of clinical medicine. With the onset of a disease, the relative content of the biomolecules of blood changes, thereby producing pathophysiological changes in the functions. Spectroscopic techniques can be effectively employed as a diagnostic tool in clinical chemistry and it can be an alternate method in clinical analysis. In the present work FTIR and UV-Vis spectroscopic techniques are employed to study the spectral differences between a normal healthy serum and that affected with some diseases like diabetes, cholesterol, thyroid and urea. The internal standards among the absorption peaks are calculated in both the methods and it is found to be an indicator to differentiate a normal from a diseased serum sample.